BRONKOPNEUMONIA - Sakila Ersa Putri Hts; Dika Amalia (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Pneumonia is a form of acute respiratory infection most often caused by viruses or bacteria. It can cause mild to life-threatening illness in people of all ages, but it is the single largest cause of infectious death in children worldwide (1). Pneumonia killed more than 808,000 children under 5 years of age in 2017, accounting for 15% of all deaths of children under 5 years. (1). It is known that the results of Basic Health Research (Riskesdas) in 2013 also showed a high prevalence of pneumonia in toddlers, namely 4.5 per 100 toddlers. This means, 4.5 out of 100 toddlers suffer from pneumonia (2). The lungs are made up of tiny sacs called alveoli, which fill with air when a healthy person breathes. When a person has pneumonia, the alveoli fill with pus and fluid, which makes breathing painful and limits oxygen intake. This infection is generally spread by direct contact with an infected person (1)